Palladium Nanoparticles Encaged in a Nitrogen‐Rich Porous Organic Polymer: Constructing a Promising Robust Nanoarchitecture for Catalytic Biofuel Upgrading. Issue 13 (23rd May 2017) - Singuru, Ramana; Dhanalaxmi, Karnekanti; Shit, Subhash Chandra; Reddy, Benjaram Mahipal; Mondal, John
Abstract: Robust nanoarchitectures based on surfactant‐free ultrafine Pd nanoparticles (NPs) (2.7–8.2±0.5 nm) have been developed by using the incipient wetness impregnation method with subsequent reduction of Pd II species encaged in the 1, 3, 5‐triazine‐functionalized nitrogen‐rich porous organic polymer (POP) by employing NaBH4, HCHO, and H2 reduction routes. The Pd‐POP materials prepared by the three different synthetic methods consist of virtually identical chemical compositions but have different physical and texture properties. Strong metal–support interactions, the nanoconfinement effect of POP, and the homogeneous distribution of Pd NPs have been investigated by performing 13 C cross‐polarization (CP) solid‐state magic angle spinning (MAS) NMR, FTIR, and X‐ray photoelectron spectroscopy (XPS), along with wide‐angle powder XRD, N2 physisorption, high‐resolution (HR)‐TEM, high angle annular dark field scanning transmission electron microscopy (HAADF‐STEM), and energy‐dispersive X‐ray (EDX) mapping spectroscopic studies. The resulting Pd‐POP based materials exhibit highly efficient catalytic performance with superior stability in promoting biomass refining (hydrodeoxygenation of vanillin, a typical compound of lignin‐derived bio‐oil). Outstanding catalytic performance (≈98 % conversion of vanillin with exclusive selectivity for hydrogenolysis product 2‐methoxy‐4‐methylphenol) has been achieved over the newly designed Pd‐POP catalyst under the optimized reaction conditions (140 °C, 10 bar H2 pressure), affording a turnover frequency (TOF) value of 8.51 h −1 and no significant drop in catalytic activity with desired product selectivity has been noticed for ten successive catalytic cycles, demonstrating the excellent stability and reproducibility of this catalyst system. A size‐ and location‐dependent catalytic performance for the Pd NPs with small size (1.31±0.36 and 2.71±0.25 nm) has been investigated in vanillin hydrodeoxygenation reaction with our newly designed Pd‐POP catalysts. The presence of well‐dispersed electron‐rich metallic Pd sites and highly rigid cross‐linked amine‐functionalized POP framework with high surface area is thought to be responsible for the high catalytic activity and improvement in catalyst stability. Abstract : POP goes the nanoparticle : Robust nanoarchitectures based on surfactant‐free ultrafine Pd nanoparticles (NPs) were developed by using the incipient wetness impregnation method with subsequent reduction of the Pd II species encaged in the 1, 3, 5‐triazine‐functionalized nitrogen‐rich porous organic polymer (POP) by NaBH4, HCHO, and H2 . Strong metal–support interactions, the nanoconfinement effect of POP, and the homogeneous distribution of Pd NPs have been investigated along with the catalysts' effectiveness in the hydrodeoxygenation of vanillin, a typical compound of lignin‐derived bio‐oil.